1994
DOI: 10.1016/0378-1097(94)00169-3
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella bronchiseptica dermonecrotizing toxin stimulates protein synthesis in an osteoblastic clone, MC3T3-E1 cells

Abstract: The effects of Bordetella bronchiseptica dermonecrotizing toxin on protein synthesis in an osteoblastic clone, MC3T3-E1 cells, were investigated. The rate of protein synthesis in the serum-starved cells was increased by the toxin after a latent period of about 4 h, and reached 2.5 times that of the control 24 h after addition of toxin. The toxin raised the level of protein synthesis even in actively proliferating cells. The stimulatory effect of the toxin on protein synthesis occurred earlier than other toxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…In vitro studies have shown that purified DNT from B. bronchiseptica induces dramatic morphological changes, stimulates DNA replication, and impairs differentiation and proliferation in osteoblastic clone MC 3T3 cells (369,372). Recent evidence indicates that these effects are due to DNT-mediated activation of the small GTP-binding protein Rho (371), which results in tyrosine phosphorylation of focal adhesion kinase (p125 fak ) and paxillin (436).…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…In vitro studies have shown that purified DNT from B. bronchiseptica induces dramatic morphological changes, stimulates DNA replication, and impairs differentiation and proliferation in osteoblastic clone MC 3T3 cells (369,372). Recent evidence indicates that these effects are due to DNT-mediated activation of the small GTP-binding protein Rho (371), which results in tyrosine phosphorylation of focal adhesion kinase (p125 fak ) and paxillin (436).…”
Section: Virulence Determinantsmentioning
confidence: 99%
“…B. bronchiseptica DNT produces dermonecrosis when injected intradermally into many animals including guinea pigs, mice, and rabbits and is lethal for mice when given intravenously (15). In cell cultures, DNT stimulates DNA and protein synthesis and assembly of actin stress fibers while inhibiting cell division, resulting in polynucleation of cells (19,20). It mediates these changes through modification and activation of the small GTP-binding protein, Rho (18).…”
mentioning
confidence: 99%
“…B. bronchiseptica DNT affects cultured cells; in particular, it inhibits alkaline phosphatase activity and reduces the type I collagen accumulation, both of which are linked to osteoblastic differentiation in an osteoblastic cell line, MC3T3-E1. Thus, impairment of the ability of osteoprogenitor cells to differentiate may result in decreased bone formation and may at least partially explain the nasal turbinate atrophy seen (16). DNT also stimulates DNA and protein synthesis in MC3T3-E1 cells but inhibits cell division, resulting in the formation of polynucleated cells (19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…B. bronchiseptica DNT is considered to be responsible for turbinate atrophy in swine atrophic rhinitis (4,6,9). The turbinate atrophy caused by DNT likely results from a deficiency of osteoblastic differentiation in bone tissues (9,11).…”
mentioning
confidence: 99%